Recent strategies for the development of oral medicines for the treatment of visceral leishmaniasis. Issue 7 (11th May 2020) - de Souza, Myla Lôbo; Gonzaga da Costa, Lucas Amadeu; Silva, Emerson de Oliveira; de Sousa, André Luiz Moreira Domingues; dos Santos, Widson Michael; Rolim Neto, Pedro José
Abstract: Considered prevalent in many countries on five continents, especially in low‐income regions, leishmaniasis is a neglected tropical disease classified by World Health Organization as one of the diseases for which the development of new treatments is a priority. It is an infectious disease caused by protozoa of the genus Leishmania, whose species may cause different clinical manifestations, such as cutaneous and visceral leishmaniasis (VL). Treatment is exclusively by drug therapy, as it has not been possible to develop vaccines yet. Currently available drugs are not fully effective in all cases; they have parenteral administration and exhibit a number of serious and very common adverse effects. The only oral drug available is expensive and it is not available in many endemic countries. Injectable administration is the main problem of treatments, since it requires patients to go to health centers, hospitalization and professional administration, which are conditions that are not adapted to the reality of the poverty conditions of patients with the disease. In this context, the development of an oral medicine has become a focus as it may solve many of these issues. Based on this scenario, this review aimed to investigate which therapeutic alternatives have been studied for the development of oral drugs directed to the treatment of human VL.